Open and/or laparoscopic one-stage resections of primary colorectal cancer and synchronous liver metastases: An observational study. Issue 11 (19th March 2021) - Nozawa, Hiroaki; Ishizawa, Takeaki; Yasunaga, Hideo; Ishii, Hiroaki; Sonoda, Hirofumi; Emoto, Shigenobu; Murono, Koji; Sasaki, Kazuhito; Kawai, Kazushige; Akamatsu, Nobuhisa; Kaneko, Junichi; Arita, Junichi; et al.
Abstract : Abstract: One-stage resections of primary colorectal cancer and liver metastases have been reported to be feasible and safe. Minimally invasive approaches have become more common for both colorectal and hepatic surgeries. This study aimed to investigate outcomes of these combined surgical procedures among different approaches. We retrospectively analyzed patients diagnosed as having primary colorectal cancer with synchronous liver metastases and who underwent 1-stage primary resection and hepatectomy with curative intent in our hospital. According to the surgical approach for the primary tumor and hepatic lesions, namely open laparotomy (Op) or laparoscopic approach (Lap), patients were classified into Op-Op, Lap-Op (laparoscopic colorectal resection plus open hepatectomy), and Lap-Lap groups, respectively. Clinicopathological factors were reviewed, and short- and long-term outcomes were compared among the groups. The Op-Op, Lap-Op, and Lap-Lap groups comprised 36, 18, and 17 patients, respectively. The superior/posterior hepatic segments were more frequently resected via an open approach. There was no laparoscopic major hepatectomy. The median volume of intraoperative blood loss was smaller in the Lap-Lap and Lap-Op groups (290 and 270 mL) than in the Op-Op group (575 mL, P = .008). The hospital stay after surgery was shorter in the Lap-Lap and Lap-Op groups (median: 17 days and 15 days, vs 19 days for the Op-Op group, P = .033). The postoperative complication rates and survivals were similar among the groups. Application of laparoscopy to 1-stage resections of primary colorectal cancer and liver metastases may offer advantages of enhanced recovery from surgical treatment, given appropriate patient selection.